THE USE OF TASK-BASED LEARNING TO DEVELOP ENGLISH SPEAKING ABILITY OF FIFTH YEAR STUDENTS OF MIN 1 TELADAN PALEMBANG - Tia Paramaditha (Edukasi, 2015)
The main problem of this thesis was to find out whether or not there is any significant difference on students’ scores who were taught using TBL method at the fifth grade students of MIN 1 Teladan Palembang. The population of this study consisted of 120 fifth grade students of MIN 1 Teladan Palembang in academic year 2012/2013. The samples were taken by using convenience sampling method consisting of 40 students from fifth grade students at MIN 1 Teladan Palembang in the academic year of 2012/2013. A descriptive method was used in this study. The data were obtained by means of oral test only. The result of the test was analyzed by using quantitative research. Based on the results of the data analysis, there were two findings, namely (1) there was no a negative progress from the students’ result of pretest and posttest in experimental group. (2) the students speaking score in experimental group were lower than students’ speaking score in control group. The writer also found most of the control group’s students got better than the experimental group’s students in speaking ability. This means that the teaching English by using Task-Based Learning Method in teaching speaking to fifth grade students of MIN 1 Teladan Palembang is not effective on their speaking ability. In conclusion, there was no a significant difference between students ability of students who were taught by using Task-Based Learning method and those who are not. Finally, it is expected that the teachers of English use various teaching method in order to develop students’ speaking ability.